2016
DOI: 10.1177/0044118x15626063
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Religious Involvement in African American and Caribbean Black Adolescents’ Experiences of Racial Discrimination

Abstract: For many Black adolescents, racial discrimination increases the risk of developing adverse psychological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 79 publications
1
41
2
Order By: Relevance
“…PD has a well-established negative effect on the mental health of adults [ 43 , 44 , 45 , 46 ] and adolescents [ 47 , 48 , 49 , 50 ]. For African American youth, discrimination operates as a specific source of stress [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…PD has a well-established negative effect on the mental health of adults [ 43 , 44 , 45 , 46 ] and adolescents [ 47 , 48 , 49 , 50 ]. For African American youth, discrimination operates as a specific source of stress [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the negative effect of discrimination on the mental health of adults is well documented [ 2 , 11 , 14 , 15 ], fewer studies have focused on the negative influence of discrimination on the mental health of Black youth [ 16 , 17 , 18 , 19 ]. In Black youth, discrimination is linked to stress [ 19 ], low self-esteem [ 18 , 19 ], and psychiatric disorders [ 20 ]. Discrimination is also associated with depressive symptoms [ 18 , 19 ] as well as clinical depression [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Black youth, discrimination is linked to stress [ 19 ], low self-esteem [ 18 , 19 ], and psychiatric disorders [ 20 ]. Discrimination is also associated with depressive symptoms [ 18 , 19 ] as well as clinical depression [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has noted the important role of religion for African Americans in terms of coping with racial discrimination (Bierman, 2006;Ellison, Musick, & Henderson, 2008;Butler-Barnes et al, 2016). Religious organizations such as churches often help in addressing discriminatory laws and practices within African American communities, using the power of their faith to uplift and sustain those individuals in the face of racial discrimination, prejudice, and exclusion due to race.…”
Section: Individual Factors and Changes In Religious And Spiritualitymentioning
confidence: 99%
“…Research has found that these discriminatory experiences can have a variety of negative impacts in the lives of ethnic minority adolescents and young adults (e.g., Brody et al, 2006;Chavous, Rivas-Drake, Smalls, Griffin & Cogburn, 2008). Although these negative experiences can have deleterious effects on African American adolescents and young adults (Schmitt, Branscombe, Postmes, & Garcia, 2014;Butler-Barnes et al, 2016), protective factors and coping processes help buffer these negative experiences (Greer & Chwaliaz, 2007;Chapman & Steger, 2010;Murry, Heflinger, Suiter, & Brody, 2011).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%